Validation of garlic extract effects using bacterial reverse mutation study (AMES) in Salmonella Typhimurium TA98 and TA100 strains - ARIGILA SESHAIAH; KING SOLOMON EBENEZER; KING SOLOMON EBENEZER (International Journal of Pharma and Bio Sciences, 2018)
The study was evaluated to validate the potential anti-mutagenic effects in garlic extracts using two different known strong positive controls (2-nitrofluorene and sodium azide) with two different Salmonella typhimurium strains (TA98 and TA100). Subsequently, 2-nitrofluorene mutagen exhibited 36 fold increases in reverting colonies in TA98 and sodium azide mutagen with 11 fold increases in TA100. Using of different concentrations as 1, 2, 4 and 5µL/plate of aqueous garlic extracts and conferred various degrees of anti-mutagenic effect on the tester strains. Exhibited maximum anti-mutagenic effects at a concentration of 5uL/plate with 78%, 4uL/plate with 70%, 2uL/plate with 50% and 1uL/plate with 38% reduction in revertant colonies in TA98 strain. Similarly, TA 100 strain, 72 % in 5uL/plate, 67 % 4uL/plate, 62% in 2uL/plate and 48% in 1uL/plate revertant reduction. According to the observation the garlic extracts having potential activity towards anti-mutagenic nature.